Research and analysis on the crotch comfort of the male boxer underwear under thermohydro environment. Issue 1 (28th November 2018) - Cheng, Pengpeng; Chen, Daoling
Abstract : Purpose: The purpose of this paper is to analyze the fit and thermal and moisture comfort factors to provide some reference value for the functional design of underwear. Design/methodology/approach: The body size data of 100 male youths are measured to analyze the body shape of the lower body. Based on the complete body size, the authors selected the matching underwear, and obtained the relevant data for the mathematical model of thermal and moisture using Grey correlation analysis method. Findings: In allusion to the defect of fit comfort and thermal-moisture comfort of the crotch, this paper presented a mathematical model, and experimental results showed that breathable fabric and breathable volume are the key factors. Originality/value: It was clarified that which is the key to the thermal and moisture comfort. At the same time, male lower body characteristics index is clear.